Genetic associations of leptin-related polymorphisms with systemic lupus erythematosus (2015)
Leptin is abnormally elevated in the plasma of patients with systemic lupus erythematosus (SLE), where it is thought to promote and/or sustain pro-inflammatory responses. Whether this association could reflect an increased genetic susceptibility to develop SLE is not known, and studies of genetic associations with leptin-related polymorphisms in SLE patients have been so far inconclusive. Here we genotyped DNA samples from 15,706 SLE patients and healthy matched controls from four different ancestral groups, to correlate polymorphisms of genes of the leptin pathway to risk for SLE. It was found that although several SNPs showed weak associations, those associations did not remain significant after correction for multiple testing. These data do not support associations between defined leptin-related polymorphisms and increased susceptibility to develop SLE. © 2015 Elsevier Inc.